Política econômica e desindustrialização no Brasil: os impactos da política macroeconômica na desindustrialização brasileira no interstício temporal 1990 - 2010 - Santos, Rodolfo Strifezzi dos (2019)
This dissertation has the objective study the loss of power of the industry to lead the Brazilian economic grow since 1990 until 2010, attributing this phenomenon to a process of deindustrialization. The research starts from the hypothesis that this was generated by macroeconomic policies, as well as by the Dutch disease. It’s taken into account too, in this work, that the political framework impacts in the retraction of the industry portion at the national product. The investigation also shows that the process of the Brazilian deindustrialization get stronger in 1990. But not ends in 2010, but yes, in this year the decline in participation of the industry in the Brazilian GDP reaches a level even more profound. Because of this was delimited the temporal interstice. As historically the productive sector of the economy is evidenced like the inductor of the economic development, this relation is studied. Even more, because the economic development it’s a consequence of economic growth, it’s approached too how real sector contributes for the sustained economic growth. The objective in this matter, is identify the importance of the industry for the economic growth. The hypothesis is that it’s even possible the economic growth without the industrial sector be your driving force, but this doesn’t happen in a sustained way. Therefore, it has an inseparable relationship between industry and economic development